Pengaruh Kepatuhan Minum Obat terhadap Pengendalian HbA1c pada Pasien Diabetes Melitus Tipe 2: Tinjauan Sistematis Berdasarkan Metode Pengukuran Kepatuhan - Diana, Ina Kusuma; Wiedyaningsih , Chairun; Kurniawati , Fivy (Journal of Pharmaceutical and Sciences, 2026)
Type 2 diabetes mellitus (T2DM) is a major public health concern in Asia, where rapid urbanization and lifestyle changes have contributed to a marked increase in disease prevalence. Poor medication adherence remains a major barrier to achieving optimal glycemic control, leading to an increased risk of complications and greater healthcare burden. This systematic review aimed to examine the relationship between medication adherence and glycated hemoglobin (HbA1c) levels among patients with T2DM, compare the strength of this association across different adherence measurement methods, and identify key factors influencing adherence and glycemic control in Asian populations. A literature search was conducted in PubMed, Europe PMC, Scopus, and ScienceDirect for cross-sectional studies published between January 2015 and April 2025. Eligible studies included adult patients with T2DM who reported medication adherence (e.g., MMAS-8, pill counts) and HbA1c outcomes. Data were synthesized narratively, and study quality was assessed using standardized appraisal tools. Of the 584 records screened, 14 studies met the inclusion criteria. Most studies demonstrated a significant inverse association between medication adherence and HbA1c levels, with stronger associations observed when objective or multidimensional adherence measures were used. Reported adherence levels varied substantially across studies, with the proportion of high adherence ranging from 3.7% to over 58%, depending on the measurement method. Mean HbA1c values ranged from 6.4% to 9.2%. Higher educational level, greater self-efficacy, and supportive healthcare environments were associated with better adherence. In contrast, psychological distress, regimen complexity, and comorbidities were linked to lower adherence and poorer glycemic control. Medication adherence is a critical determinant of glycemic control among patients with T2DM in Asia. The choice of adherence measurement method influences the observed association with HbA1c. Interventions should address psychosocial and clinical barriers and incorporate culturally adapted, multidimensional adherence assessment approaches.